The Effect Financial Knowledge, Financial Attitude, and Income on Financial Behavior Through Locus of Control in Students - Reseky Aprilianto Budiman; Haryanto Tanuwijaya; Candraningrat Candraningrat; Antok Supriyanto (Universitas 17 Agustus 1945 Surabaya, 2024)
This research aims to determine the effect of financial knowledge, financial attitude, and income towards financial behavior through locus of control as an intervening variabel in students. This research uses a quantitative approach by distributing questionnaires to 240 respondents from the Faculty of Economics and Business, majoring in Management and have taken financial management courses at private campus in Surabaya. The research is tested using SmartPLS 4 student version with Partial Least Sqsuare Strucktural Equation Modeling (PLS-SEM) analysis.